The AP1 Transcription Factor Fosl2 Promotes Systemic Autoimmunity and Inflammation by Repressing Treg Development - Renoux, Florian; Stellato, Mara; Haftmann, Claudia; Vogetseder, Alexander; Huang, Riyun; Subramaniam, Arun; Becker, Mike O.; Blyszczuk, Przemyslaw; Becher, Burkhard; Distler, Jörg; Kania, Gabriela; Boyman, Onur; et al. (Cell Reports, 2020)
Regulatory T cells (Tregs) represent a major population in the control of immune homeostasis and autoimmunity. Here we show that Fos-like 2 (Fosl2), a TCR-induced AP1 transcription factor, represses Treg development and controls autoimmunity. Mice overexpressing Fosl2 (Fosl2tg) indeed show a systemic inflammatory phenotype, with immune infiltrates in multiple organs. This phenotype is absent in Fosl2tg × Rag2−/− mice lacking T and B cells, and Fosl2 induces T cell-intrinsic reduction of Treg development that is responsible for the inflammatory phenotype. Fosl2tg T cells can transfer inflammation, which is suppressed by the co-delivery of Tregs, while Fosl2 deficiency in T cells reduces the severity of autoimmunity in the EAE model. We find that Fosl2 could affect expression of FoxP3 and other Treg development genes. Our data highlight the importance of AP1 transcription factors, in particular Fosl2, during T cell development to determine Treg differentiation and control autoimmunity.
CRIS-Team Scopus Importer:2020-07-03
Keywords: autoimmunity; FoxP3; immunology; inflammation; mouse models; regulatory T cells; T cells